Studi Model Kinetika Ekstraksi Berbantu Ultrasonik pada Lada (Piper nigrum L.) - Anggie Yulia Sari; I Wayan Budiastra; Slamet Widodo (PERTETA, 2021)
Ultrasonic Assisted Extraction (UAE) is used to extract oleoresin from pepper that offer a competitive method compared to maceration. This research was aimed to study and to validate a second order of kinetics model of UAE white pepper extraction that can describe the relationship between oleoresin yield, UAE amplitude, and extraction time. Pepper is milled to particle size of 100 mesh. Then the 200 g of powder of pepper is poured to ethanol of 800 ml (1:4) to subjected to UAE extraction. A maceration process is also carried out as control. Amplitude and extraction times used in the UAE extraction are 45, 60, 75, and 90%; and 45, 60, 75, and 90 minutes. The value of white pepper oleoresin concentration experiment (Ct) with model calculations is closely related to the extraction capacity at saturation (Cs) and the resulting extraction rate constant (k). The value of Cs between 29,24–34,48 g/l and the value of k ​​between l/g.minute. The results from the two Ct obtained produce a correlation coefficient value of 0.85 and the error value between 0,18–14,09 %. The second-order kinetic model developed can be used to predict the yield of UAE-assisted white pepper oleoresin with UAE amplitude limit conditions of 45–90 % and extraction time of 45–90 minutes.